Latitudinal variation in macroalgal consumption by fishes on the Great Barrier Reef - Bennett, Scott; Bellwood, D. (2011)
On coral reefs, herbivory is a key factor in maintaining coral-dominated systems. Despite this, few studies have investigated the process of herbivory over broad spatial scales. We examined the patterns of herbivory across sites spanning 900 km along the Great Barrier Reef (GBR), Australia. Assays were used to directly quantify the removal rates of the brown macroalgae Sargassum, while feeding rates of herbivorous fishes were measured using remote underwater video. Removal rates of Sargassum by herbivores exhibited a significant regional decline from north to south, driven primarily by changes in the behaviour of the 4 most dominant species and to a lesser extent by a regional decline in herbivore diversity. Whilst the 4 species (Naso unicornis, Kyphosus vaigiensis, Siganus doliatus and S. canaliculatus) consistently dominated feeding, jointly accounting for 85, 99 and 98% of mass standardised bites within the north, central and southern regions, respectively, they recorded over an order of magnitude fewer bites in the south. Interestingly, the decline in bites and the lower feeding diversity was not a result of lower herbivore biomass or density in the southern region. Rather, the major difference between fish herbivory among regions was the eeding propensity of the 4 dominant feeders toward the transplanted Sargassum. Reefs with intact and structurally comparable herbivore communities therefore cannot be assumed to have the same realized functional impact on the reef. Local behaviour may be an important factor. © 2011 Inter-Research.